ANALISIS MINAT DAN FAKTOR YANG MEMPENGARUHI MINAT BELAJAR SISWA PADA MATA PELAJARAN IPA BIOLOGI KELAS VIII SMP NEGERI 3 TARAKAN - Roisatul Afifa; Fitri Wijarini; Nursia Nursia (Program Studi Pendidikan Biologi Universitas Borneo Tarakan, 2021)
Abstract: This study aimed to analyze students’ interest in learning Biologi and factors that influenced the interest among the eighth grade students of SMP Negeri 3 Tarakan. This survey research used a quantitative descriptive approach. The subjects were 74 students of the SMP Negeri 3 Tarakan, teachers of science subject and parents of students. Data ware collected by distributing online questionnaires with two repetitions, interviewing the teachers and the parents, and observations during learning. The collected data ware analyzed quantitatively and descriptively. The results showed that in the first repetition, the students’ interest level in the material of the digestive system was moderate with a percentage value of 70.27% or a frequency of 52 students. Meanwhile, in the second repetition, students’ interest level on the material of the digestive system was moderate with a percentage value of 66.21% or a frequency of 49 students. Factors that influenced student interest in the first repetition repetition were subject matter (48.64%), facilities and infrastructure (63.51%), student activities with the community (64.78%), categorized as quite influential. In the second repetition, factors that affected student interest were the subject matter (54.05%) and student activities with the community (63.51%), cantegorized as quite influential. So, it could be concluded that the interest of student with two repetitions was in the moderate category, while the dominant factors that influenced their interest were subject matter and student activities with the community. Keywords: analysis, factors that influence interest, Interest in Learning.